Polarization-insensitive 160-Gb/s wavelength converter with all-optical repolarizing function using circular-birefringence highly nonlinear fiber - Tanemura, T; Lee, JH; Wang, DX; Katoh, K; Kikuchi, K (OPTICAL SOC AMER, 2006)
A circular-birefringence highly nonlinear fiber (CB-HNLF) with the nonlinear coefficient of 12/W/km is fabricated successfully by twisting a commercial silica-based highly nonlinear fiber. Using the cross-phase modulation in a 100-m-long CB-HNLF and subsequent optical filtering, we realize error-free pulsewidth-maintaining wavelength conversion of 160Gb/s signal with only 0.7-dB polarization sensitivity. In addition to the simplicity and stability, the demonstrated scheme features an ultrafast repolarizing functionality, where the degree-of-polarization of the input signal is restored in an all-optical manner. These advantages make the scheme highly attractive to be employed in the future photonic networks. (c) 2006 Optical Society of America.
Keywords: CROSS-PHASE MODULATION; DISPERSION-SHIFTED FIBER; TWISTED FIBER; CONVERSION; XPM